Re: Appointing an architectural coordinator to fulfill the obligations under conditions of contract sub-clause 8.1 & 15.1 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the appointment of architectural coordinator according to the contract for BRACU new campus project.